DEVELOPMENT OF GUIDED DISCOVERY-BASED LEARNING TOOLS USING HYPERCONTENT TO IMPROVE STUDENTS' MATHEMATICAL CRITICAL THINKING ABILITY - Maulidia Wanahari; Zul Amry; elmanani simamora (Prima: Jurnal Pendidikan Matematika, 2022)
Online learning (in the network) is learning online through specified media. This study aims to: 1) describe how the level of validity, practicality and effectiveness of guided discovery-based learning tools using Hypercontent to improve critical mathematical thinking skills at SMAN 1 Tambangan; 2) describe the improvement of students' mathematical critical thinking skills using guided discovery-based learning tools using Hypercontent at SMAN 1 Tambangan The method used in this research is development research. The subjects in this study were the 11th grade students SMAN 1 Tambangan in the academic year 2021/2022. The results showed that 1) Guided discovery-based learning tools using hypercontent to improve students' mathematical critical thinking skills that were developed already met the criteria of being valid, practical and effective; 2) The improvement of mathematical critical thinking skills using guided discovery-based learning tools using hypercontent that has been developed seen from the N-gain value in the first trial of 0.33 increased to 0.4 in the second trial, meaning that it is in the "medium" category.